Coherence Analysis of EEG Under Emotional Stimuli Related to Mental States. Issue 8 (9th July 2014) - Asakawa, Tetsuya; Hayashi, Takuto; Mizuno‐Matsumoto, Yuko
SUMMARY: The objective of this research is to abstract the differences of the brain functional reaction in mental states by using coherence analysis in electroencephalography (EEG). Twenty‐two healthy subjects were assessed for their psychosomatic states using the Cornell Medical Index (CMI) and were divided into two groups: normal (I) and preneurotic (II‐IV). The EEG was measured during emotional tasks (relaxed, pleasant, and unpleasant sessions) using audio‐visual stimuli and was analyzed using coherence analysis. The coherence values of the preneurotic group in the θ band in 120 s to 150 s of the pleasant and unpleasant sessions and in the β band in the relaxed session were significantly larger than the values of the normal group. The coherence values of the normal and preneurotic groups in the α2 band in 30 s to 60 s and 90 s to 120 s in the unpleasant sessions were significantly larger than the values in the relaxed session. The increase in θ activity suggests that an intuitive and irrational response to the emotional situation would appear, and the β activity indicates that attention would be paid more to external than to internal situations in the preneurotic group. The alpha activity shows that the mentally internal response to the unpleasant situation would be prompt in the normal group, while in contrast the response would be delayed in the preneurotic group. These results suggest that the information processing of emotional stimuli in the brain differ depending on the mental state.